UNDERGRADUATE MATHEMATICS STUDENTS' UNDERSTANDING OF THE CONCEPT OF FUNCTION - Bardini, Caroline; Pierce, Robyn; Vincent, Jill; King, Deborah (Journal on Mathematics Education, 2014)
Concern has been expressed that many commencing undergraduate mathematics students have mastered skills without conceptual understanding. A pilot study carried out at a leading Australian university indicates that a significant number of students, with high tertiary entrance ranks, have very limited understanding of the concept of function, despite the emphasis it receives in the secondary mathematics curriculum. Whilst most students were familiar with families of functions, many were unable to give an appropriate definition or recognize whether a given graph or rule represents a function; and could not make correct connections between function graphs and tables of values.Keywords: Algebra, Functions, Secondary School Mathematics, Undergraduate Mathematics